CRISPR/Cas12a-based biosensing platform for the on-site detection of single-base mutants in gene-edited rice - Wang, Mengyu; Liu, Xiaojing; Yang, Jiangtao; Wang, Zhixing; Wang, Haoqian; Wang, Xujing (Frontiers in Plant Science, 2022)
At present, with the acceleration of the global biotechnology industry revolution, the novel transgenic technologies represented by gene editing are developing rapidly. A large number of gene-edited products featuring a single base or a few bases indels have been commercialized. These have brought great challenges to traditional nucleic acid detection technology and the safety regulation of genetically modified organism (GMO). In this study, we developed an instrument-free CRISPR/Cas12a-based biosensing platform named Cas12aFVD (fast visual detection) that couples with recombinase polymerase amplification (RPA) for on-site detection of gene-edited rice in one-pot. The detection procedure can be accomplished in 40 min with a visible result, which can be observed by the naked eyes under blue light (470-490 nm). According to the accurate recognition of target based on CRISPR/crRNA, Cas12aFVD exhibits excellent performance for the detection of two and three bases deletion, one base substitution and one base insertion with a limit detection of 12 copies/μL, showing great potential for mutant detection, especially single-base mutant. The Cas12aFVD biosensing platform is independent of laboratory conditions, making it a promising and pioneering platform for future detection of gene-edited products.